Metabolic engineering of phosphite metabolism in Synechococcus elongatus PCC 7942 as an effective measure to control biological contaminants in outdoor raceway ponds - Sandra Isabel González-Morales; Navid Berenice Pacheco-Gutiérrez; Carlos A. Ramírez-Rodríguez; Alethia A. Brito-Bello; Priscila Estrella-Hernández; Luis Herrera-Estrella; Damar L. López-Arredondo (Biotechnology for Biofuels, 2020)
Abstract Background The use of cyanobacteria and microalgae as cell factories to produce biofuels and added-value bioproducts has received great attention during the last two decades. Important investments have been made by public and private sectors to develop this field. However, it has been a challenge to develop a viable and cost-effective platform for cultivation of cyanobacteria and microalgae under outdoor conditions. Dealing with contamination caused by bacteria, weedy algae/cyanobacteria and other organisms is a major constraint to establish effective cultivation processes. Results Here, we describe the implementation in the cyanobacterium Synechococcus elongatus PCC 7942 of a phosphorus selective nutrition system to control biological contamination during cultivation. The system is based on metabolic engineering of S. elongatus to metabolize phosphite, a phosphorus source not normally metabolized by most organisms, by expressing a bacterial phosphite oxidoreductase (PtxD). Engineered S. elongatus strains expressing PtxD grow at a similar rate on media supplemented with phosphite as the non-transformed control supplemented with phosphate. We show that when grown in media containing phosphite as the sole phosphorus source in glass flasks, the engineered strain was able to grow and outcompete biological contaminants even when the system was intentionally inoculated with natural competitors isolated from an irrigation canal. The PtxD/phosphite system was successfully used for outdoor cultivation of engineered S. elongatus in 100-L cylindrical reactors and 1000-L raceway ponds, under non-axenic conditions and without the need of sterilizing containers and media. Finally, we also show that the PtxD/phosphite system can be used as selectable marker for S. elongatus PCC 7942 transgenic strains selection, eliminating the need of antibiotic resistance genes. Conclusions Our results suggest that the PtxD/phosphite system is a stable and sufficiently robust strategy to control biological contaminants without the need of sterilization or other complex aseptic procedures. Our data show that the PtxD/phosphite system can be used as selectable marker and allows production of the cyanobacterium S. elongatus PCC 7942 in non-axenic outdoor reactors at lower cost, which in principle should be applicable to other cyanobacteria and microalgae engineered to metabolize phosphite.